2019
DOI: 10.1016/j.jsams.2018.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations of fundamental movement skills with objectively measured physical activity and sedentariness during school transition from primary to lower secondary school

Abstract: The results of this study indicated that supporting opportunities for girls' engagement in both MVPA and leaping skill development activities during their primary school education is strongly recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 22 publications
2
30
0
5
Order By: Relevance
“…Based on the review inclusion criteria and data availability, 521 studies were further excluded. Thus, 52 studies met the inclusion criteria and were included in the quantitative analysis representing a total sample of 22,091 children and adolescents (Figure ; PRISMA flow diagram). A subset of 31 studies with exactly 1 year of follow‐up data were included in the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the review inclusion criteria and data availability, 521 studies were further excluded. Thus, 52 studies met the inclusion criteria and were included in the quantitative analysis representing a total sample of 22,091 children and adolescents (Figure ; PRISMA flow diagram). A subset of 31 studies with exactly 1 year of follow‐up data were included in the meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…In the current sample, compared to MC, HRF acted as a much stronger predictor of future PA. While MC is undoubtedly an important factor for PA engagement, it is possible that HRF is more important in promoting involvement in PA. Involvement in PA can of course in turn subsequently allow for development of MC [73] and further enhancements in HRF [1]. In a study examining adolescents involvements with the ball during recreational soccer matches, Ré et al (2016) [74] found that HRF, along with agility, was the strongest predictor of involvements with the ball, while soccer specific technical skills did not significantly contribute to an individual's involvement.…”
Section: Discussionmentioning
confidence: 99%
“…In both genders, MVPA levels decrease with age [11], especially during adolescence [12]. Most of the existing studies has found the decline of MVPA in children and adolescents [9,10,[13][14][15][16][17][18][19]], but did not take into account the differences in maturity. The decrease of MVPA may extend into adulthood [12,20,21] and seems to be more associated with biological age than with chronological age [22].…”
Section: Introductionmentioning
confidence: 97%